Understanding Associations Between Family Rejection, Human–Animal Interaction, and Mental Health Among LGBTQ+ Emerging Adults - Angela Matijczak; Shelby E. McDonald; Lori R. Kogan; Rosalie Corona; Katlyn Reynolds (Pets)
Many LGBTQ+ emerging adults experience rejection from their family of origin. Family rejection is a stressor that contributes to worsened mental health for LGBTQ+ emerging adults. Supportive relationships with others can be an important protective factor for LGBTQ+ emerging adults as they cope with family rejection. The bond and interactions LGBTQ+ pet owners have with their pets may provide love, comfort, and support, similar to the relationship they may have with a human attachment figure. This quantitative study aimed to test pet attachment as a moderator of the association between family rejection and mental health in a sample of LGBTQ+ emerging adults. We collected survey data from 201 18–25-year-old LGBTQ+ pet owners living in the state of Virginia. After testing several moderation models using the PROCESS macro in SPSS, we found that pet attachment was not a significant moderator of the relation between family rejection and mental health symptoms (i.e., depression, anxiety, psychological distress). The findings suggest that pet attachment may not be a protective factor for LGBTQ+ emerging adults who experience family rejection, although these findings should be interpreted in light of the characteristics of our sample and limitations of the study. We recommend that future researchers explore alternative moderators or test these associations among LGBTQ+ individuals in other developmental periods.